Soluble Neuregulin1 Down-Regulates Myelination Genes in Schwann Cells - El Soury, Marwa; Fornasari, Benedetta E.; Morano, Michela; Grazio, Elio; Ronchi, Giulia; Incarnato, Danny; Giacobini, Mario; Geuna, Stefano; Provero, Paolo; Gambarotta, Giovanna (Frontiers in Molecular Neuroscience, 2018)
Peripheral nerves are characterized by the ability to regenerate after injury. Schwann cell activity is fundamental for all steps of peripheral nerve regeneration: immediately after injury they de-differentiate, remove myelin debris, proliferate and repopulate the injured nerve. Soluble Neuregulin1 (NRG1) is a growth factor that is strongly up-regulated and released by Schwann cells immediately after nerve injury. To identify the genes regulated in Schwann cells by soluble NRG1, we performed deep RNA sequencing to generate a transcriptome database and identify all the genes regulated following 6 hours stimulation of primary adult rat Schwann cells with soluble recombinant NRG1. Interestingly, the gene ontology analysis of the transcriptome reveals that NRG1 regulates genes belonging to categories that are regulated in the peripheral nerve immediately after an injury. In particular, NRG1 strongly inhibits the expression of genes involved in myelination and in glial cell differentiation, suggesting that NRG1 might be involved in the de-differentiation (or “trans-differentiation”) process of Schwann cells from a myelinating to a repair phenotype. Moreover, NRG1 inhibits genes involved in the apoptotic process, and up-regulates genes positively regulating the ribosomal RNA processing, thus suggesting that NRG1 might promote cell survival and stimulate new protein expression. This in vitro transcriptome analysis demonstrates that in Schwann cells NRG1 drives the expression of several genes which partially overlap with genes regulated in vivo after peripheral nerve injury, underlying the pivotal role of NRG1 in the first steps of the nerve regeneration process.